SAVINGS RATIO, THE IMPACT OF READING INFORMATION - Belinda Xarba; Etleva Peta; Alketa Bejko (European Scientific Journal, ESJ, 2015)
Personal financial ratios are an important indicator of a family's financial situation. By calculating the level of the financial report, the family can analyze its financial situation and can predict its financial performance in the future. Savings ratio is one of personal financial ratios, recognizing and calculating the recommended level of this ratio as well as keeping this ratio closer to recommended levels serves as a foundation for achieving a better financial situation in the future. The aim of this paper is to identify the families whose managers have read too much about personal finance management are more likely to achieve the recommended level of savings ratio. In order to achieve this aim was studied a vast literature of national and foreign researchers, where it was concluded that there is no recommended level of savings ratio as well as to other ratios of personal finance discussed in any academic study for Albania. Considering this observation to calculate the recommended level of saving ratio was referred foreign researchers, who recommended a "guide" about this ratio and its level, "guide" which we refer throughout this paper. The absence of alternative data led us to make questionnaires in order to collect the necessary information. After the data was collected and refined for their elaboration were used the programs Microsoft Office Excel and Spss Ibm Statistics. For testing was used statistical methods Chi - square test.